2000
DOI: 10.1063/1.1330752
|View full text |Cite
|
Sign up to set email alerts
|

Size dependence of the exchange bias field in NiO/Ni nanostructures

Abstract: NiO/Ni wires have been investigated as a function of their width in order to investigate the size dependence of exchange bias. The samples have been prepared by e-beam lithography and ion milling of ion beam sputtered thin films. For NiO/Ni wires narrower than 3 m, the exchange bias field significantly depends on the wire width. A NiO/Ni film shows an exchange bias field of Ϫ78 Oe whereas the exchange bias field of wires narrower than 200 nm is reduced to approximately Ϫ40 Oe. The coercive field of the NiO/Ni … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
107
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 17 publications
(18 reference statements)
9
107
1
Order By: Relevance
“…The exchange bias field ⌬H C is found to vary from 80 to 700 Oe depending on the type of Ni/ NiO nanostructure. 10,27 In the present work ⌬H C is found to be Ͻ2 Oe at all temperatures, 5 to 300 K, clearly indicating that NiO is nonmagnetic in the present work and does not couple magnetically to the core Ni crystallites. The thin nonmagnetic NiO layer, however, cannot fully suppress the magnetic interactions, exchange and dipolar, between the Ni particles.…”
Section: Resultssupporting
confidence: 49%
“…The exchange bias field ⌬H C is found to vary from 80 to 700 Oe depending on the type of Ni/ NiO nanostructure. 10,27 In the present work ⌬H C is found to be Ͻ2 Oe at all temperatures, 5 to 300 K, clearly indicating that NiO is nonmagnetic in the present work and does not couple magnetically to the core Ni crystallites. The thin nonmagnetic NiO layer, however, cannot fully suppress the magnetic interactions, exchange and dipolar, between the Ni particles.…”
Section: Resultssupporting
confidence: 49%
“…Earlier works on magnetic wires were mostly concentrated on size dependence and orientation dependence on field [2,15,16]. Fraune et al [17] have investigated the size dependence of exchange bias in NiO/Ni nanostructures. They observed that for NiO/Ni wires narrower than 3 mm, the exchange bias field significantly depends on the wire width.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown in FM/AF nanostructures where the FM domain size is reduced through nanopatterning that exchange bias can be significantly altered. 8 In contrast, there have been limited experimental studies on the AF domain size dependence of exchange bias, 9 largely due to the difficulty in characterizing and manipulating AF domains in FM/AF systems. [10][11][12] The domain sizes may also affect the shape of the hysteresis loop.…”
mentioning
confidence: 99%